2019
DOI: 10.1111/jcmm.14535
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐125b in vascular diseases: An updated systematic review of pathogenetic implications and clinical applications

Abstract: Epigenetic changes, particularly non‐coding RNAs, have been implicated extensively in the pathogenesis of vascular diseases. Specific miRNAs are involved in the differentiation, phenotypic switch, proliferation, apoptosis, cytokine production and matrix deposition of endothelial cells and/or vascular smooth muscle cells. MicroRNA‐125b has been studied in depth for its role in carcinogenesis with a double‐edged role; that is, it can act as an oncogene in some cancer types and as a tumour suppressor gene in othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 92 publications
1
31
0
Order By: Relevance
“…VC was the main outcome of this study. We measured VC based on a semi-quantitative AAC scoring system using the posteroanterior chest films, according to prior studies and reviews [ 34 , 35 ]. This scoring system used to be tested and applied to our patients with CKD as well [ 29 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…VC was the main outcome of this study. We measured VC based on a semi-quantitative AAC scoring system using the posteroanterior chest films, according to prior studies and reviews [ 34 , 35 ]. This scoring system used to be tested and applied to our patients with CKD as well [ 29 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…MiR-125b has long been deemed an onco-miR and tumor suppressive miR through targeting cell survival and apoptosis-related molecules, including p53, Bcl/Bak, and PI 3 K/Akt pathways [83]; the increased expression of miR-125b was reported in multiple types of human malignancy. In vascular tissues, miR-125b over-expression leads to a lower degree of endothelial and VSMC proliferation, more vaso-relaxation, but a greater severity of inflammation, as summarized in a prior systematic review [83].…”
Section: Negative Vc-regulating Mirnasmentioning
confidence: 99%
“…MiR-125b has long been deemed an onco-miR and tumor suppressive miR through targeting cell survival and apoptosis-related molecules, including p53, Bcl/Bak, and PI 3 K/Akt pathways [83]; the increased expression of miR-125b was reported in multiple types of human malignancy. In vascular tissues, miR-125b over-expression leads to a lower degree of endothelial and VSMC proliferation, more vaso-relaxation, but a greater severity of inflammation, as summarized in a prior systematic review [83]. In terms of its effect on VC, the up-regulation of miR-125b is associated with less calcium deposition by murine and human VSMCs by directly repressing Ets-1 and osterix, an important osteoblastic marker [13,22]; furthermore, our previous work demonstrated that higher VC severity among uremic patients correlates with lower circulating miR-125b levels, supporting its anti-VC effect and its clinical applicability [33].…”
Section: Negative Vc-regulating Mirnasmentioning
confidence: 99%
“…Among these VC-related miRNAs, miR-125b is an important example; circulating miR-125b levels reportedly predict the clinical course of VC in patients with CKD. 4,5 Judging from the importance of miR-125b in vascular pathologies shown by a prior review 6 and its readiness for assay, measuring circulating miR-125b levels for vascular risk estimation may bear high clinical utility. However, determinants of circulating miR-125b levels remain unclear.…”
Section: Dear Editormentioning
confidence: 99%